Managing animal trypanosomosis in Africa: Issues and options - Omamo, Steven Were; D'Ieteren, G.D.M. (2003)
This paper discusses past and present approaches to managing tsetse-transmitted animal trypanosomosis in Africa and describes the three main weaknesses of these approaches, i.e., inappropriate objectives, inadequate links between research and policy-making and a lack of recognition that trypanosomosis should be high up on the social science research agenda. Making progress in managing trypanosomosis has been difficult and the authors argue that the weaknesses of the approaches must be corrected if Africa is to benefit from the few advances made so far, and for the continent to make further sustained efforts to combat the disease. The authors explain that this can be achieved by replacing the current widespread preoccupation among researchers and policymakers with controlling (or eradicating) trypanosomosis with a focus on managing (or coping with) the disease. In addition, ways of achieving greater coherence between research and policy-making must be explored. Finally, the social science issues raised by the question of which practical steps need to be taken to manage trypanosomosis in Africa should be placed at the forefront of research efforts.